2023
DOI: 10.3126/jcmsn.v19i1.53460
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Moraxella Catarrhalis and it's Antibiotics Susceptibility Patterns from Different Respiratory Tract Infection Patient's Clinical Samples

Abstract: IntroductionMoraxella catarrhalis is a gram negative, oxidase positive, cocci mainly causing upper and lowerrespiratory tract infections. The RND family efflux pumps lead to multidrug resistance in most ofthe gram negative bacteria. One of the well- known pumps in M. catarrhalis is arcAB and oprMsystem. The objective of this study was to investigate the antibiotic resistance in M. catarrhalis andto determine its resistance dependence on the efflux pump. MethodsIn this study, 283 different respiratory tract inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…32 In this study, PCR was positive in 98% of the processed nail specimens. This finding agreed with Jha et al 19 in India who found that 100% of 231 phenotypically-confirmed onychomycosis cases were genotypically positive by PCR. On the other hand, lower positive results of PCR (67%) were detected by another study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…32 In this study, PCR was positive in 98% of the processed nail specimens. This finding agreed with Jha et al 19 in India who found that 100% of 231 phenotypically-confirmed onychomycosis cases were genotypically positive by PCR. On the other hand, lower positive results of PCR (67%) were detected by another study.…”
Section: Discussionsupporting
confidence: 92%
“…Approximately, similar results had been published by other studies conducted in Egypt, 17,18 and other countries as in India, Pakistan and Iraq. 1,19,20 According to current results, the prevalence of onychomycosis had been shown to be significantly higher in patients with concomitant diseases such as anemia (46%), diabetes mellitus (25%) and PVD (20%) a finding which came in line with that reported by Emam and Abd El-salam 18 in Egypt and Dogra et al 21 in India. Also, in this study, toenails (60%) were more affected than fingernails (40%) and the observed patterns of onychomycosis were DLSO (38%), TDO (24%), PO (20%) and WSO (18%), these were in agreement with that published by Mohtady et al 22 in Egypt and Gautam et al 14 in India.…”
Section: Discussionsupporting
confidence: 88%